2019
DOI: 10.1111/ped.13963
|View full text |Cite
|
Sign up to set email alerts
|

Motor trajectories of preterm and full‐term infants in the first year of life

Abstract: Background: Motor development occurs throughout periods of motor skill acquisition, adjustment and variability. The objectives of this study were to analyze and compare biological and health characteristics and motor skill acquisition trajectories in preterm and full-term infants during the first year of life. Methods: Two thousand, five hundred and seventy-nine infants (1,361 preterm) from 22 states were assessed using the Alberta Infant Motor Scale. Multivariate General Linear Model, t-tests, ANOVA, and Tuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Hence, this may be a reason for discrepancies between studies investigating motor function. Although we know that motor trajectories between term-born and preterm infants are somewhat different ( 34 ), and the term-born infants in our sample had higher ASQ-2 scores, excluding preterm infants from our sample did not affect the outcome of the linear regression analysis.…”
Section: Discussionmentioning
confidence: 81%
“…Hence, this may be a reason for discrepancies between studies investigating motor function. Although we know that motor trajectories between term-born and preterm infants are somewhat different ( 34 ), and the term-born infants in our sample had higher ASQ-2 scores, excluding preterm infants from our sample did not affect the outcome of the linear regression analysis.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, detecting motor delay at an early stage, and, in particular, motor delays in gross motor skills, and implementing effective interventions could reduce the impact of impaired early motor skills on later development, both within the motor domain, and across other domains ( Spittle et al, 2008 ). As underscored recently, interventions on preterm infants should be carried out beyond the first months of life and should include guidelines for parents and caregivers on motor development ( Valentini et al, 2019 ). Along these lines, a meta-analysis by Spittle et al (2012) suggested that interventions focusing on preterm infants (e.g., physiotherapy), and their parents (e.g., parent–infant relationships) had a positive impact on motor development and cognitive development, improving outcomes in these domains during infancy and preschool age.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies describe developmental outcomes among infants born with microcephaly whose mothers were infected by ZIKV during pregnancy 12,[16][17][18] . Yet, little is known about these children's long-term development, raising concern particularly for their mothers [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…We obtained raw scores by centile ranks, concerning infant's age and total score (abnormal if lower than 5 th ; suspected if between 5 th and 25 th ; typical if above 25 th ) 16 . The test took on average 20 minutes per child and was recorded for further analysis of children's motor performance in the four positions.…”
Section: Methodsmentioning
confidence: 99%